Human embryonic stem cells contribute to embryonic and extraembryonic lineages in mouse embryos upon inhibition of apoptosis - Wang, Xuepeng; Li, Tianda; Cui, Tongtong; Yu, Dawei; Liu, Chao; Jiang, Liyuan; Feng, Guihai; Wang, Lei; Fu, Rui; Zhang, Xinxin; Hao, Jie; Wang, Yukai; et al. (Cell research, 2018)
Dear Editor, Recently, interspecies chimera formation has been established in rodents by injection of rat pluripotent stem cells （PSCs） into mouse early embryos, and such a system provides an in vivo assay to test the developmental potential of human PSCs （hPSCs） [1]. In addition, the interspecies chimeras formed between hPSCs and large animal embryos would open new avenues to generate human tissues and organs for regenerative medicine [2]. In rodents, embryonic stem cells （ESCs） and epiblast stem cells （EpiSCs） have been derived from inner cell mass （ICM） of the blastocyst and post-implantation epiblast respectively [3, 4].